Perinatal exposure to environmental tobacco smoke is associated with changes in DNA methylation that precede the adult onset of lung disease in a mouse model. (24th August 2017) - Cole, Elizabeth; Brown, Traci A.; Pinkerton, Kent E.; Postma, Britten; Malany, Keegan; Yang, Mihi; Kim, Yang Jee; Hamilton Jr., Raymond F.; Holian, Andrij; Cho, Yoon Hee
Abstract: Prenatal and early-life environmental tobacco smoke (ETS) exposure can induce epigenetic alterations associated with inflammation and respiratory disease. The objective of this study was to address the long-term epigenetic consequences of perinatal ETS exposure on latent respiratory disease risk, which are still largely unknown. C57BL/6 mice were exposed to prenatal and early-life ETS; offspring lung pathology, global DNA, and gene-specific methylation were measured at two adult ages. Significant alterations in global DNA methylation and promoter methylation of IFN-γ and Thy-1 were found in ETS-exposed offspring at 10–12 and 20 weeks of age. These sustained epigenetic alterations preceded the onset of significant pulmonary pathologies observed at 20 weeks of age. This study suggests that perinatal ETS exposure induces persistent epigenetic alterations in global DNA, as well as IFN-γ and Thy-1 promoter methylation that precede the adult onset of fibrotic lung pathology. These epigenetic findings could represent potential biomarkers of latent respiratory disease risk.